2017
DOI: 10.18282/jsd.v2.it1.115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intense pulsed light in the treatment of mild-to-moderate acne vulgaris

Abstract: Acne vulgaris is a very common chronic inflammatory disease of pilosebaceous units. It can be associated with considerable loss of self-esteem and psychological morbidity when left untreated. With the emergence of lasers and intense pulsed light, long-term reduction of acne lesions is now possible. The success of these optical devices depends on the selected parameters and biologic variables of patient. The objective of this study is to determine the efficacy and safety of intense pulsed light (IPL) in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…At the end of six treatment sessions, the mean lesion count of total lesions reduced from 44.83 (at baseline) to 11.60 which was found to be statistically significant (p=.005). Our study results was in concordance with similar study done by Khan WZ et al 18 wherein mean lesion count of total lesions decreased to 7.48 ± 3.34 of their pretreatment value (14.49 ± 2.93) after final treatment session which was statistically significant (p=.000). At the end of six treatment sessions (week 6), 3 patients (10.0%) had excellent non inflammatory lesion clearance (>75%), 16 patients (53.3%) had good non inflammatory lesion clearance (51-75%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the end of six treatment sessions, the mean lesion count of total lesions reduced from 44.83 (at baseline) to 11.60 which was found to be statistically significant (p=.005). Our study results was in concordance with similar study done by Khan WZ et al 18 wherein mean lesion count of total lesions decreased to 7.48 ± 3.34 of their pretreatment value (14.49 ± 2.93) after final treatment session which was statistically significant (p=.000). At the end of six treatment sessions (week 6), 3 patients (10.0%) had excellent non inflammatory lesion clearance (>75%), 16 patients (53.3%) had good non inflammatory lesion clearance (51-75%).…”
Section: Discussionsupporting
confidence: 93%
“…At the end of six treatment sessions (week 6), 17 patients (56.7%) had excellent total lesion clearance (>75%), 13 patients (43.3%) had good total lesion clearance (51-75%). However, similar study done by Mohanan S et al 19 wherein seven patients had 51-75% reduction in lesion count (good response) and one had moderate response at the end of five treatment sessions; Khan W Z et al 18 reported 6 patients (8%) having excellent response and 33 patients (44%) showing good response at the end of treatment.…”
Section: Discussionmentioning
confidence: 65%
“…In our study, only 9% of patients developed transient mild erythema, less than the study by Khan et al where 21% of the patients developed erythema. 13 Mohanan et al reported no adverse effects in their trial. This further establishes the safety of IPL in South Asian skin.…”
Section: Discussionmentioning
confidence: 87%
“…12 Previous studies reported an improvement of >50% in 44% of patients. 13,14 per week for four weeks, and results revealed that a majority of patients (85%) had more than 50% improvement in their acne vulgaris lesions. 15 Using a higher cut-off filter of 530nm to 1200nm with six passes over the affected area could explain the difference in clinical outcome.…”
Section: Discussionmentioning
confidence: 99%